2016
DOI: 10.1080/14760584.2017.1242419
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the costs and benefits of pneumococcal vaccination in adults

Abstract: Pneumococcal infection is a public health concern that disproportionately affects the young, the elderly, and the immunocompromised. There is an open debate on the implementation of polysaccharide and/or conjugate vaccines for pneumococcal diseases in adults and the elderly in many countries. The aim of this paper is to systematically review the economic profile of pneumococcal vaccines in adults in terms of costs and benefits. Areas covered: The search for economic studies on pneumococcal vaccination was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…Vaccination programs will become increasingly important around the world in the future due to the constant aging of the population, and prevention may reduce the burden of pneumococcal diseases on health systems and the consequent incremental social costs. In light of these considerations, pneumococcal vaccines are a paradigmatic example of a clear and effective trade-off between benefits and costs [ 95 , 96 ]. PCV13 and PPV23 have an excellent value for money and should become a real priority for decision makers in public health [ 97 ].…”
Section: Medical Costsmentioning
confidence: 99%
“…Vaccination programs will become increasingly important around the world in the future due to the constant aging of the population, and prevention may reduce the burden of pneumococcal diseases on health systems and the consequent incremental social costs. In light of these considerations, pneumococcal vaccines are a paradigmatic example of a clear and effective trade-off between benefits and costs [ 95 , 96 ]. PCV13 and PPV23 have an excellent value for money and should become a real priority for decision makers in public health [ 97 ].…”
Section: Medical Costsmentioning
confidence: 99%
“…40 This study also revealed alcohol abuse as a risk factor for mortality. Pneumococcal vaccination with PCV13 or PPV23 in adults is cost-effective and should be considered a priority for decision-makers, 41 and status of vaccination varied widely among studies (0-54.5%). Pneumonia vaccination was another effective means of preventing IPD, but much work remains to be done to increase the acceptance of pneumonia vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Emergent admission to ICU is a strong predictor of subsequent critical illness 14 ; both the acute care costs and future costs related to worsening chronic health burden in this cohort are high 15 . The health economics would seem to strongly support making all reasonable efforts to improve modifiable health factors in this population 16 .…”
Section: Discussionmentioning
confidence: 99%